(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Article spatiotemporal update of Culture of Kazakhstan analyzed with four time points of view of philosophical knowledge. 1) If we take a historical perspective, the traditions of the Kazakh culture from ancient times up customs, ceremonies. 2) In ХҮІІІ-ХХ centuries the culture of the Kazakh people impacted policy of Tsarist Russia, in recent times the ideology of the communist party, which weakened the characteristics of the national culture from the inside. 3) 1990-2015 years in independent Kazakhstan national culture and ethnic relations have been developed on the new basis. 4) The fourth period covers 2015-2050 years. In the future, will double the contribution of the development strategy of Kazakhstan, the impact of such a move, as is currently the central category of modernization of national culture is a human. In the future, has to return the status of the Kazakh state. Therefore, to characterize and evaluate the history and culture of the Kazakh people, are in Eurasia, one size fits all, is the one-sided approach. East and West had on the formation of the Kazakh culture inhomogeneous influence in every age differently. In unstable conditions change social development real life and human values and can not find one vector of development. Nevertheless, the key to success in force of society and the fundamental principle of the people’s forces in unity, harmony, in a fair service to the people. Paying tribute to the fate of the people, make some points in the history of thinking. Key words: national culture, cultural modernization, continuity, humanism, social system, social harmony, national identity, national security